2011
DOI: 10.1136/bmj.d3736
|View full text |Cite
|
Sign up to set email alerts
|

Association between provision of mental illness beds and rate of involuntary admissions in the NHS in England 1988-2008: ecological study

Abstract: Objective To examine the rise in the rate of involuntary admissions for mental illness in England that has occurred as community alternatives to hospital admission have been introduced. Design Ecological analysis.Setting England, 1988England, -2008 Data source Publicly available data on provision of beds for people with mental illness in the National Health Service from Hospital Activity Statistics and involuntary admission rates from the NHS Information Centre. Main outcome measuresAssociation between annual… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
93
2

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 102 publications
(98 citation statements)
references
References 14 publications
3
93
2
Order By: Relevance
“…116,117 Many previous studies of the excess detention of BME patients have been from London, which may not be representative of other areas of the UK. A large study of 22 psychiatric hospitals in England found no association between ethnicity and patient perceptions of coercion at admission or during the first 4 weeks of inpatient stay.…”
Section: Discussionmentioning
confidence: 99%
“…116,117 Many previous studies of the excess detention of BME patients have been from London, which may not be representative of other areas of the UK. A large study of 22 psychiatric hospitals in England found no association between ethnicity and patient perceptions of coercion at admission or during the first 4 weeks of inpatient stay.…”
Section: Discussionmentioning
confidence: 99%
“…The number of in-patient beds is now little more than a third of the number 20 years ago. 15 Typically, each team determines its own case-load, criteria for accepting and discharging patients and how long it will care for them. Each phase of care is dealt with by a different set of professionals.…”
Section: Research Into Practice and Its Unintended Consequencesmentioning
confidence: 99%
“…Acute services are under particular pressure in the United Kingdom; a shortage of beds seems to be triggering a rise in involuntary admissions (Keown, Weich, Bhui, & Scott, 2011) and over-occupancy is affecting quality and safety (The Royal College of Psychiatrists, 2011). The consensus around improving recovery-focused care also resonates with evidence that the current amount and quality of therapeutic interaction available is likely to be reducing service-users' well-being and opportunities for recovery.…”
Section: Feedback Groupsmentioning
confidence: 99%